Ultrafast studies of electron injection in Ru dye sensitized SnO2 nanocrystalline thin film - Christophe Bauer; Gerrit Boschloo; Emad Mukhtar; Anders Hagfeldt (International Journal of Photoenergy)
By using two-color femtosecond transient absorption spectroscopy, we have measured the electron injection rate for bis(tetrabutylammonium) cis di(thiocyanato) bis (2,2’-bypiridine-4,4’ carboxylic acid)Ruthenium (II) dye (called N719) into SnO2 nanocrystalline thin films. The electron injection rate has been measured by monitoring the formation of the dye oxidized state and the arrival of electrons in the conduction band. Dynamics of electron injection are multiexponential (0.2, 4 and 130 ps) and are therefore slower than the N719-ZnO or N719-TiO2 systems. The photocurrent action spectrum of N719-SnO2 shows a quantum efficiency of 0.65 at 530 nm proving that efficient charge separation can take place despite of the relatively slow electron injection rate.